Characteristics of Hearing Impairment in Patients with Suspected Congenital Rubella Syndrome at the ENT Clinic of Prof. Dr. I.G.N.G Ngoerah Hospital Denpasar, Indonesia - Raditya, I Gede Wahyu Adi; I Made Wiranadha (Universitas Airlangga, 2024)
Asymptomatic rubella virus infection can cause delays in the diagnosis of rubella in pregnant women, leading to the development of congenital rubella syndrome (CRS). The clinical manifestations of congenital rubella syndrome are called the rubella triad, which includes heart problems, eye problems, and hearing disorders. Sensorineural hearing loss is the most common type of hearing loss in children with rubella infection. This study aimed to determine the characteristics of hearing loss in CRS patients. This study used a retrospective descriptive research design, utilizing secondary data from the medical records of patients with CRS who underwent hearing examinations at the Ear, Nose, Throat (ENT) Polyclinic of Prof. dr. I.G.N.G. Ngoerah Hospital Denpasar, Indonesia. The study found that the most common age group among suspected CRS patients was 6 - 12 months (51.42%), the majority of these patients were male (62.86%), the most frequent clinical signs and symptoms in suspected CRS patients were congenital heart disease (CHD) as a major criterion (60%), and microcephaly as a minor criterion (77.14%). Based on the CRS case criteria, none of the suspected CRS patients were diagnosed with confirmed CRS, with most cases being classified as clinical CRS (65.71%). The hearing loss in suspected CRS patients was entirely sensorineural type with the majority of cases being bilaterally and to a very severe degree (53.57%)